Media Agenda and Public Agenda: A Study of Issues during the 13th General Election - Aini Maznina, A. Manaf; Malia, Taibi; Kamaruzzaman, Abdul Manan (UKM, 2017)
Media might play an important role in public’s voting decision. Even so, it is unknown whether the media agenda counterpart public agenda with regard to the level of importance of the issues covered in the media. This study examined the issues of concern by the Malaysian mainstream newspapers, as well as the issues of concern by the public during the 13th General Election (GE 13). In particular, this study explored the relationship between media and public agenda; as well as the relationship between Malay language newspaper agenda and the Malay public agenda. Content analysis and survey were performed to fulfil these objectives. The findings showed that the media has different agenda from the public. In addition, the Malay newspaper and public of the same ethnic group do not share similar agenda of issues. On top of that, the findings showed the priority of issues perceived by media and public are different. While the public see national security as the most important issue of the country, media on the other hand, set religion and politics as the priority in their agenda.